Risk factors for self-harm repetition in adolescents: A systematic review. (August 2021) - Rahman, Farhan; Webb, Roger T.; Wittkowski, Anja
Abstract: Self-harm behavior can begin in early adolescence, with the highest rates of self-harm, between 1990 and 2000 in England, being among adolescents aged 16 to 24 years and there being considerable risk of fatal and non-fatal repetition. Previous systematic reviews have identified risk factors for self-harm in adolescents, but not for the repetition of this behavior. The aim of this review was to synthesise the psychological, psychosocial and sociodemographic risk factors for self-harm repetition in adolescents. By searching four databases, 27 studies were identified and included in the review. Several psychological (e.g., psychiatric morbidity, features of previous self-harm, psychological distress), psychosocial (e.g., alcohol misuse, poor family and peer relationships) and sociodemographic (e.g., age, gender and ethnicity) risk factors were identified for self-harm repetition in adolescents. Several risk factors across all categories for self-harm overlapped with that of self-harm repetition, such as depression, alcohol misuse and female gender. The clinical implications of these findings for practitioners were discussed. As was the case with prior reviews in this area, comparability between studies was limited and a meta-analysis was not possible due to considerable heterogeneity in outcome definitions, measures and methodologies. Highlights: This review examined risk factors for self-harm repetition risk among adolescents. Many psychological, psychosocial and sociodemographic risk factors were identified. Multiple risk factors for self-harm overlapped with self-harm repetition. Most evidence: psychological, followed by psychosocial and sociodemographic factors. Most studies measured risk factors through identifying prospective predictors.